Renewable energy sources in hot water supply system - Kuznetsova, Marta; Maliovanyy, Myroslav (Lviv Polytechnic Publishing House, 2015)
Possibility of renewable energy sources use in heat water supply system has been studied. Potential renewable energy sources to be effectively used in Lviv climatic zone have been analysed, and their main advantages and disadvantages have been shown. Efficiency of use of vacuum solar collectors and “air-water”-type heat pump in hot water supply system has been ascertained based on the analysis of performance of the facility operating at Lviv Polytechnic National University.
Keywords: energy efficiency; renewable power engineering; solar collectors; heat pump; hot water supply